Emerging Roles for Phase Separation of RNA-Binding Proteins in Cellular Pathology of ALS - Milicevic, Katarina; Rankovic, Branislava; Andjus, Pavle R.; Bataveljic, Danijela; Milovanovic, Dragomir (Frontiers in Cell and Developmental Biology, 2022)
Liquid-liquid phase separation (LLPS) is emerging as a major principle for the mesoscale organization of proteins, RNAs, and membrane-bound organelles into biomolecular condensates. These condensates allow for rapid cellular responses to changes in metabolic activities and signaling. Nowhere is this regulation more important than in neurons and glia, where cellular physiology occurs simultaneously on a range of time- and length- scales. In a number of neurodegenerative diseases, such as Amyotrophic Lateral Sclerosis (ALS), misregulation of biomolecular condensates leads to the formation of insoluble aggregates - a pathological hallmark of both sporadic and familial ALS. Here, we summarize how the emerging knowledge about the LLPS of ALS-related proteins corroborates with their aggregation. Understanding the mechanisms that lead to protein aggregation in ALS and how cells respond to these aggregates promises to open new directions for drug development.